Foreword (Georgian Journal for European Studies, 2023)
Georgia, as the nation of the ‘associated trio’, recently was granted a clear ‘European perspective’, whichtransformed the country’s long-lasting pro-EU aspirations into a tangible result of extension of EuropeanEnlargement Policy towards the Eastern Partnership region. The unprovoked invasion and aggressive warlaunched by Russia in Ukraine triggered a need across the Western countries for a ‘paradigm shift’ in globalapproaches, which created for Tbilisi a unique chance to take the steps towards EU membership. At the sametime the pressure has increased to keep the pace for the speedy democratic transformation and for theestablishment of the rules based order, where the trust of the public in democratic institutions is increased. EUactorness had always been strong in Georgia, however, these developments broadened further its scope andpresence in the country.